Perbaikan Usability Aplikasi Pemesanan Tiket Bioskop Menggunakan Metode Usability Testing dan USE Questionnaire - Moch Dian Fahmi; Hanifah Muslimah Az - Zahra; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Usability is one of the important aspects to be a benchmark for the quality of an application can be said to be good. Usability is used to measure how an application can be used according to the user's desire to achieve the desired goal, supported by the ease of the user to use the application interface. This cinema ticket booking application is an application that is used to book tickets in theaters throughout Indonesia can be accessed through applications on the Android platform. Based on the problems found in the results of user reviews on the platform there are still problems experienced by users, then usability measurement is used to measure the usability level of the application. Testing using usability testing method is done directly to the user, done by giving a task scenario. This test is carried out twice, the initial test to find out the initial usability value and the existing problems, then based on the existing problems given recommendations for improvements in the form of prototypes which are then re-tested to get the final usability value, after that the test results will be compared to get the usability value of the application this cinema ticket booking after repairs and before repairs. When testing there were three stages, namely, usability testing, filling out questionnaires and conducting interviews. Filling in the questionnaire is supported by USE Questionnare which has four parameters, namely Usefulness, Ease of Use, Ease of Learning, Satisfaction, the results of which will be processed and produce usability values ​​in this cinema ticket booking application. Improvements made refer to Material Design and Color Comparison Websites to get good recommendations. The initial test results obtained usability value of 57.4% categorized as sufficient predicate and the final test results obtained 83.1% were categorized as very good